2011
DOI: 10.1242/dev.053694
|View full text |Cite
|
Sign up to set email alerts
|

Signaling through BMP receptors promotes respiratory identity in the foregut via repression of Sox2

Abstract: SUMMARYThe mammalian foregut gives rise to the dorsally located esophagus and stomach and the ventrally located trachea and lung. Proper patterning and morphogenesis of the common foregut tube and its derived organs is essential for viability of the organism at birth. Here, we show that conditional inactivation of BMP type I receptor genes Bmpr1a and Bmpr1b (Bmpr1a;b) in the ventral endoderm leads to tracheal agenesis and ectopic primary bronchi. Molecular analyses of these mutants reveal a reduction of ventra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
188
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(210 citation statements)
references
References 60 publications
21
188
0
Order By: Relevance
“…If embryos were left in the BMPR inhibitor after lung specification between stages 35 and 42, we observed tracheal degeneration and hypoplastic lung buds (supplementary material Fig. S8), consistent with mouse studies demonstrating a role for BMP in maintenance of trachea fate and lung bud morphogenesis (Domyan et al, 2011;Lie et al, 2008). These data indicate that the failure of respiratory specification in Osr1/Osr2-depleted embryos is primarily due to elevated BMP signaling.…”
Section: Research Article Development 139 (16)supporting
confidence: 87%
See 3 more Smart Citations
“…If embryos were left in the BMPR inhibitor after lung specification between stages 35 and 42, we observed tracheal degeneration and hypoplastic lung buds (supplementary material Fig. S8), consistent with mouse studies demonstrating a role for BMP in maintenance of trachea fate and lung bud morphogenesis (Domyan et al, 2011;Lie et al, 2008). These data indicate that the failure of respiratory specification in Osr1/Osr2-depleted embryos is primarily due to elevated BMP signaling.…”
Section: Research Article Development 139 (16)supporting
confidence: 87%
“…During this process in mice, Sox2 is initially expressed throughout the foregut epithelium and then around E9.5 BMP signaling suppresses Sox2 and esophagus fate in the ventral foregut. Mutual repression between Sox2 and Nkx2.1 then resolves the two lineages (Que et al, 2006;Li et al, 2008;Domyan et al, 2011). Our data suggest that BMP has a similar role in Xenopus; BMP signaling was not required for Xenopus lung specification but is necessary to maintain later tracheal fate (supplementary material Fig.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The etiology of this congenital anomaly is still unknown; Studies in mouse models suggested a role for the BMP type I receptor genes; however causal genes in human TA are yet to be identified [5].…”
mentioning
confidence: 99%